ESG Disclosure, Firm Value, and Investment Decisions: Evidence from Indonesia’s Capital Market - Rismawati; Duriani; Muhammad Aqsa (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) disclosure on corporate value and investor choices in Indonesia's developing capital market. This research examines how ESG reporting improves transparency, reduces information asymmetry, and influences investor behavior through the lenses of signaling, stakeholder, and behavioral finance theories. Analysis of 138 firm-year observations from publicly traded non-financial corporations through multiple regression indicates that both ESG disclosure (B = 0.311; p = 0.003) and firm value (B = 0.594; p < 0.001) significantly influence investment decisions, with firm value exhibiting a more substantial impact. These findings align with focus group discussions that emphasize the significance of credible and comparable ESG narratives in fostering investor trust. This study enhances the sustainability accounting discourse by providing empirical evidence and policy implications for regulators and corporations to improve ESG disclosure standards in Indonesia.